Early life maltreatment affects intrinsic neural function in mothers - Schneider, Isabella; Neukel, Corinne; Bertsch, Katja; Fuchs, Anna; Möhler, Eva; Zietlow, Anna-Lena; Brunner, Romuald; Wolf, Robert Christian; Herpertz, Sabine (Journal of psychiatric research, 2021)
Early life maltreatment (ELM) has an impact on brain functions involved in parenting and is associated with impaired maternal sensitivity. Here, we investigated the influence of ELM on intrinsic neural function and its associations with maternal sensitivity in mothers without a current episode of a mental disorder. Twenty-seven mothers with ELM and 29 mothers without ELM were examined using resting-state functional magnetic resonance imaging, followed by Amplitude of Low Frequency Fluctuations, regional homogeneity and seed-based functional connectivity analyses. Videotaped interactions between mothers and their school-aged children were conducted to assess maternal sensitivity based on the Emotional Availability Scales. Regional and functional connectivity measures were used to investigate associations between intrinsic activity and emotional availability. Mothers with ELM showed reduced maternal sensitivity and lower intrinsic neural activity in the right superior frontal gyrus, the left precuneus, the left middle occipital gyrus, and the parietal cortex (left angular and right supramarginal gyrus) compared to mothers without ELM (p < .001, whole-brain). Amplitude of Low Frequency Fluctuations in the superior frontal gyrus was positively associated with maternal sensitivity across all participants (p = .002). The data suggest a behavioral and neural signature of ELM even in currently mentally healthy mothers. In particular, effects of ELM were found in distinct brain regions involved in social cognition and executive control. These ELM-related alterations may be associated with maternal behavior.
Gesehen am 24.12.2021